P209 Outcomes of partner notification (PN) for sex partners of people with chlamydia, managed via the Online Chlamydia Pathway. (30th June 2016) - Gibbs, Jo; Sonnenberg, Pam; Tickle, Laura; Sutcliffe, Lorna; Gkatzidou, Voula; Hone, Kate; Aicken, Catherine; Tariq Sadiq, S; Estcourt, Claudia
Abstract : Background/introduction: Within the e STI 2 consortium, we conducted exploratory studies of an innovative Online Chlamydia Pathway ( OCP : results service, automated clinical consultation, electronic prescription via community pharmacy, with telephone helpline support), which included optional online partner management. Aim(s)/objectives: To evaluate PN outcomes and sex partner uptake of online management. Methods: Participants: untreated GUM clinic attenders (two London services) and people tested through six London NCSP online postal testing areas: 21.07.14–13.3.15. The OCP offered index patients an SMS/email containing a unique code and link to forward to partners permitting them to access online care via OCP (patient referral). Outcomes were captured by OCP and index-reported at telephone follow-up (2 weeks post diagnosis) Results: Outcomes : 221 index patients consented to the study and 172 (78%) were followed up by telephone (median age 23, 62% female). These 172 index patients reported 371 partners; 317/371 (85%) were contactable and 256/317 (81%) of these were notified. Index patients reported 120/317 (38%) as treated. Online outcomes: 154 index patients reached PN stage of OCP (some had already been routed to clinic). 94/154 (61%) requested online partner access. They reported 280 partners: 28 went online; 19 received treatment at their chosen pharmacy; and 4 were treated elsewhere. Discussion/conclusion: 38% of partners treated compares favourably with outcomes for routine PN within similar studies. Online management of sex partners through patient referral is feasible but uptake was low and most successful PN was achieved offline. Pathway optimisation could include anonymised sex-partner PN messaging and provision of partner STI self-sampling kits.